Gene panel sequencing improves the diagnostic work-up of patients with idiopathic erythrocytosis and identifies new mutations - Camps, C; Petousi, N; Bento, C; Cario, H; Copley, R; McMullin, M; vanWijk, R; Ratcliffe, P; Robbins, P; Taylor, J (Ferrata Storti Foundation, 2016)
Erythrocytosis is a rare disorder characterized by increased red cell mass and elevated hemoglobin concentration and hematocrit. Several genetic variants have been identified as causes for erythrocytosis in genes belonging to different pathways including oxygen sensing, erythropoiesis and oxygen transport. However, despite clinical investigation and screening for these mutations, the cause of disease cannot be found in a considerable number of patients, who are classified as having idiopathic erythrocytosis. In this study, we developed a targeted next generation sequencing panel encompassing the exonic regions of 21 genes from relevant pathways (~79Kb) and sequenced 125 patients with idiopathic erythrocytosis. The panel effectively screened 97% of coding regions of these genes, with an average coverage of 450X. It identified 51 different rare variants, all leading to alteration of protein sequence, with 57 out of 125 cases (45.6%) having at least 1 of these variants. Ten of these were known erythrocytosis-causing variants, which had been missed following existing diagnostic algorithms. Twenty-two were novel variants in erythrocytosis-associated genes (EGLN1, EPAS1, VHL, BPGM, JAK2, SH2B3) and in novel genes included in the panel (e.g. EPO, EGLN2, HIF3A, OS9), some with high likelihood of functionality, for which future segregation, functional and replication studies will be useful in providing further evidence for causality. The rest were classified as polymorphisms. Overall, these results demonstrate the benefits of using a gene panel versus existing methods where focused genetic screening is performed depending on biochemical measurements: it improves diagnostic accuracy and provides the opportunity for novel variant discovery.